Socioeconomic status and problem behaviors in young Chinese children: A moderated mediation model of parenting styles and only children - Lin, Xunyi; Zhang, Yifan; Liao, Yutong; Xie, Wanlin (Frontiers in Psychology, 2023)
Introduction This study tested a moderated mediation model of child number (CN) and parenting styles (PS) in the relationships between family socioeconomic status (SES) and young children’s problem behaviors (PB). Methods A sample of 1,101 children (Mage = 4.90 years, SD = 1.07) and their parents participated in this study. Parents reported on PS, SES, and children’s PB. Results and Discussion The results show SES was positively related to authoritative parenting and negatively related to authoritarian parenting; problem behaviors were negatively related to authoritative parenting and positively related to authoritarian parenting; authoritative parenting and authoritarian parenting mediated the relationship between SES and PB; and singleton moderated the relationship between SES and PB. The combination of only children and low levels of SES could lead to high PB levels, while the combination of non-only children and high levels of SES could lead to high PB levels. At the same SES, only children had higher PB levels than non-only children.